(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
the article mainly analyzes the functions, methods, management decisions and social factors of educational management. The objectively observed, recurring interactions of different components and connections in the management process are reflected in forms of educational management. Therefore, expressions such as forms of management in education, knowledge, strategic planning and its subject, principles, incentives in education, methods, laws, functions, planning, management, design are expressed with deep information in the article. Also, the experience of international countries with developed educational management was studied, and information was provided about its application in our country.